2016
DOI: 10.1155/2016/8370132
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction Model for Membrane Proteins Using Moments Based Features

Abstract: The most expedient unit of the human body is its cell. Encapsulated within the cell are many infinitesimal entities and molecules which are protected by a cell membrane. The proteins that are associated with this lipid based bilayer cell membrane are known as membrane proteins and are considered to play a significant role. These membrane proteins exhibit their effect in cellular activities inside and outside of the cell. According to the scientists in pharmaceutical organizations, these membrane proteins perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 38 publications
(36 reference statements)
0
33
0
Order By: Relevance
“…There are many feature extraction methods and algorithms developed for predicting biological features. For example, Butt et al used statistical moments to extract features and Multilayer Neural Network (MNN) to predict membrane proteins [ 38 ], Akmal et al extracted the protein feature with multiple methods and combined with MNN to identify glycosylation sites [ 39 ], and Ehsan et al used neuro network for classification of signal peptides [ 40 ]. With our dataset, the amino acid location feature extraction method and the SVM algorithm were employed to perform prediction.…”
Section: Discussionmentioning
confidence: 99%
“…There are many feature extraction methods and algorithms developed for predicting biological features. For example, Butt et al used statistical moments to extract features and Multilayer Neural Network (MNN) to predict membrane proteins [ 38 ], Akmal et al extracted the protein feature with multiple methods and combined with MNN to identify glycosylation sites [ 39 ], and Ehsan et al used neuro network for classification of signal peptides [ 40 ]. With our dataset, the amino acid location feature extraction method and the SVM algorithm were employed to perform prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Raw moments are neither scale-invariant nor location-invariant [ 6 , 21 & 22 ]. The central moments also provide similar information, but these moments are computed along the centroid of the data, which makes it location invariant with respect to the centroid nonetheless it is still scale-variant [ 21 , 22 & 23 ]. Hahn moments are based on Hahn polynomials; these moments are neither scale-invariant nor location-variant.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have made numerous contributions in developing several computational models to predict an attribute of a protein [ 8 ]. Studies showed that attributes of a protein are reliant not only on the composition of amino acids but also on the sequence in which amino acids occur in the polypeptide chain [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several properties of data are described by different orders of moments. Some moments are used to reveal eccentricity and orientation of data while some are used to estimate the data size [45]- [48]. Several moments have been formed by various mathematicians and statisticians based on famous distribution functions and polynomials.…”
Section: Statistical Momentsmentioning
confidence: 99%